ANALISIS KONTEN POST INSTAGRAM TERHADAP ONLINE ENGAGEMENT: (Studi Kasus pada Lima Coffee Shop di Kota Bandung Tahun 2020) - Flaviana, Aneu Karlob; Syahputra, Syahputra (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2021)
This research is based on the background to find out how the influence of post type on online engagement in five coffee shops in Bandung and how the effect of posting time on online engagement in the five coffee shops. In addition, this study also aims to find recommendations for managing posts in five coffee shop accounts to increase online engagement. This research uses quantitative methods with descriptive research type by taking post data uploaded by five Instagram coffee shop accounts from September 2018 to August 2019 to be used as research objects. The posts analyzed in this study totaled 448 posts. Data analysis techniques in this study are descriptive analysis and different tests of Kruskal Wallis and Post Hoc.The results of this study indicate that the type of post and time of posting (month and day), only the month has a significant influence on online engagement, while the day has no significant effect on likes and comments. The posting time of the month that has the most significant influence on likes and comments is January, May, June, and August. The type of post information has the most significant effect on likes and comments compared to other post types. Keywords: Social Media; Instagram; Online Engagement.